Green Entrepreneurship Development Strategy Based On Local Characteristic To Support Eco-Tourism Continuous - Soenarto, Rahmawati, Anastasia Riani Suprapti, Rum Handayani, Putu Sudira (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2019)
The development of ecotourism can not be separated from the empowerment of local communities and small and medium enterprises (SMEs). The purpose of this research is to develop ecotourism development and planning model, especially the relationship between ecotourism and sustainable community development through green entrepreneurship development strategy by highlighting local uniqueness as the main weapon to enhance the attractiveness of ecotourism destination in NTB Province. Results of primary and secondary data collection have obtained SWOT picture which is useful to make the draft of village tourism policy in lombok NTB. Green Village based tourism entreprenuership and local wisdom to enhance tourist attraction to Lombok NTB: Output, governance system of green entrepreneur development and Tourism Village in NTB province, consisting of (a) Policy of developing green entrepreneur and tourism village for ecotourism destination development (b) Action Plan green entrepreneur and green product (c) Planning Indicators and (d) Monitoring and evaluation system.